Structure and depth profile composition analysis of Cr/(B4C)/V/(B4C) multilayer for water window application. (June 2016) - Li, Pin; Huang, Qiushi; Jiang, Li; Li, Wenbin; Fei, Jiani; Zhu, Jie; Zhang, Zhong; Wang, Zhanshan
Abstract: Ultrathin B4 C barrier layers have been recently used to reduce the interface widths of soft X-ray Cr/V multilayers and improve the reflectance at the water window region. To further study the chemical changes in the multilayer induced by the barrier layers, Cr/V multilayers (period equals to 4 nm) with and without B4 C barrier layers were characterized by grazing incidence X-ray reflectometry (GIXR) and X-ray photoelectron spectroscopy (XPS). The GIXR results show that the B4 C barrier layers significantly reduce the interface widths of the 4 nm-period Cr/V multilayer as already observed for the short-period multilayer. The XPS depth profile confirms an enhanced elemental contrast between Cr and V in the multilayer with B4 C, as compared to the one with no barriers. According to the fitting results of the photoelectron peaks, the compound formation of VB2, extra VC and B4 C were found in the structure with barrier layers. These compounds help suppress the interdiffusion between Cr and V and contribute to the small interface widths of the multilayer. Highlights: The interface widths of a 4 nm-period Cr/V multilayers are reduced by using B4 C barrier layers. XPS results display an enhanced elemental contrast between Cr and V after the introduction of B4 C barrier layers. VB2, extra VC and the B4 C compound were found in the multilayer which help to reduce the interface widths.